The Construction of Women’s Image and the Narrative of Nationalism among Face veiled-University Students in West Nusa Tenggara - Wardatun, Atun; Wahid, Abdul (Sawwa: Jurnal Studi Gender, 2020)
This article discusses the image of women and nationalism in the view of 15 female students of the Islamic Religious University (PTKI) in West Nusa Tenggara behind their face-veils (cadar). Methodologically, this study encourages the interpretation of facts from the perspective of the agents by involving the voices of women as subjects who are able to describe their choices and explain their actions responsibly. The choice of female university students as subjects for veil-related research is short among the general trends of research on veils targeting women from militant groups. This research reveals the meaning of the veil as a dynamic and open contestation of women’s identity, gender ideology, and nationalism. The dynamics and openness are possible due to the fact that female students are still in the formation phase of identities while veiling existence nowadays more about fashion trends and lifestyle. The dynamics appear in the ambiguity of the self-image of women they hold by placing women as sources of defamation (fitnah) as well as being pillars of the state. Openness is seen in the narrative of their nationalism which is wrapped in a strong inclusive and tolerant attitude, in addition to the tendency of exclusivism and conservatism of a small number of them. The findings of this study contribute to ideas for emancipatory movements such as gender equality and strengthening nationalism. The movements are to continue to be active and more creative in offering alternatives to the establishment of those female students’ identity and ideology in a more progressive direction.